Chemical compound structures and the higher dimension of molecules emerging research and opportunities - Zhizhin, G. V. (Gennadiĭ Vladimirovich) (Engineering Science Reference, 2018)
"This book proves that virtually very much chemical compounds have the structure of a higher dimension. It gives an impulse for the analysis of the interaction of molecules specific substances as objects of higher dimension. This is especially important, for example, in nanomedicine, nanotoxicology and quantum biology"--